The Utilization of Livestock Dung as A Biogas Starter from Water Hyacinth to Suppress Water Weeds - Edi Muhammad Jayadi; Nurrahmah Nurrahmah (Jurnal Penelitian Pendidikan IPA, 2022)
Animal manure and water hyacinth will become waste in the environment if not utilized. One form of utilization of both is to make it as raw material for biogas. The aims of this study were: to determine the effect of the type of manure on the process of forming biogas from water hyacinth, which is related to: 1) the speed of biogas formation, 2) the temperature of the slurry , 3) the pH of the slurry , and 4) the volume of biogas produced. This study was designed with a completely randomized design (CRD), consisting of five (5) treatments, namely Treatment 1 (P 1 ) cow dung + water hyacinth + water, (P 2 ) buffalo dung + water hyacinth + water, (P 3 ) manure goat + water hyacinth + water, (P 4 ) horse manure + water hyacinth + water, and (P 5 ) broiler chicken manure + water hyacinth + water. Each treatment was repeated 4 times to obtain 20 experimental units. In this study, the composition of the mixture of raw materials was used as follows: 8 kg of chopped water hyacinth (2 cm) + 3 kg of animal dung + 2 liters of water. This is based on the results of research by Sari et al. (2014) which showed that the composition was good enough to produce biogas made from water hyacinth. The composition of the raw material mixture is as follows: 8 kg of chopped water hyacinth (2 cm) + 3 kg of animal dung + 2 liters of water. The variables observed in this study were: the rate of gas formation, slurry pH, slurry temperature, and the volume of gas produced. The research was conducted at the Biology Science Education Laboratory, Faculty of Tarbiyah and Teacher Training, UIN Mataram. The time of research was carried out from March to October 2018. The results showed that the type of manure only had a significant effect on the amount of biogas formed, but did not significantly affect the time of gas formation, slurry pH, and slurry temperature. Thus, the five types of manure can be used as a starter in the manufacture of biogas made from water hyacinth.